Re-evaluating the mythical divide between traditional and novel cardiovascular risk factors in rheumatoid arthritis - Eirik Ikdahl; Mats Julius Stensrud (RMD Open)
Cardiovascular (CV) risk factors for rheumatoid arthritis (RA) are conventionally classified as ‘traditional‘ and ‘novel‘. We argue that this classification is obsolete and potentially counterproductive. Further, we discuss problems with the common practice of adjusting for traditional CV risk factors in statistical analyses. These analyses do not target well-defined effects of RA on CV risk. Ultimately, we propose a future direction for cardiorheumatology research that prioritises optimising current treatments and identifying novel therapeutic targets over further categorisation of well-known risk factors.